2012
DOI: 10.1007/s10803-012-1533-9
|View full text |Cite
|
Sign up to set email alerts
|

Is Talent in Autism Spectrum Disorders Associated with a Specific Cognitive and Behavioural Phenotype?

Abstract: Parents of 125 children, adolescents and young adults with autism spectrum disorders completed a newly developed questionnaire aimed at identifying cognitive and behavioural characteristics associated with savant skills in this group. Factors distinguishing skilled individuals were then further investigated in case studies of three individuals with exceptional skills for music, art and mathematics. The findings from the case studies largely confirmed the results from the questionnaire study in showing that spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 39 publications
2
32
0
1
Order By: Relevance
“…Estimates of the prevalence of savant abilities among persons on the autism spectrum range from 1/200 (Hermelin, 2001) to 1/3 or even higher when not distinguished from peaks of ability (Bennett and Heaton, 2012;Howlin et al, 2009). A prevalence of 10% was classically reported by Rimland (1978) based on a postal survey of 5400 parents of autistic children that included questions about special abilities related to music, memory, numbers, and art.…”
Section: Prevalence and Specificity Of Domain-specific Abilities In Amentioning
confidence: 99%
See 2 more Smart Citations
“…Estimates of the prevalence of savant abilities among persons on the autism spectrum range from 1/200 (Hermelin, 2001) to 1/3 or even higher when not distinguished from peaks of ability (Bennett and Heaton, 2012;Howlin et al, 2009). A prevalence of 10% was classically reported by Rimland (1978) based on a postal survey of 5400 parents of autistic children that included questions about special abilities related to music, memory, numbers, and art.…”
Section: Prevalence and Specificity Of Domain-specific Abilities In Amentioning
confidence: 99%
“…In a study with a large cohort of autistics, Howlin et al (2009) found that 28.5% of the participants met criteria for a savant skill based on parental reports, and 17% met criteria for an exceptional skill within Wechsler intelligence scales. In a parental questionnaire screening, Bennett and Heaton (2012) found that 42% of a sample of 125 AS children and adolescents were reported by their caregivers to possess a skill that contrasted with their overall level of functioning. Among the AS persons in the database of the Specialized Clinic for Pervasive Developmental Disorders of Rivière-des-Prairies Hospital, savant abilities, as defined by the Autism Diagnostic Interview-Revised (ADI-R; Lord et al, 1994), were found in 45.3% (143/316) of AS individuals with speech onset delay or anomalies, and in 72.9% (97/133) of AS individuals without speech delay.…”
Section: Prevalence and Specificity Of Domain-specific Abilities In Amentioning
confidence: 99%
See 1 more Smart Citation
“…ASD is most often investigated from the perspective of its core deficits, yet there is growing evidence to suggest that individuals with the disorder can also demonstrate cognitive strengths (Baron-Cohen et al 2009; Bennett and Heaton 2012). Mathematics represents one of a handful of skills routinely reported as a savant talent in autism, and indeed some individuals with ASD have shown extraordinary powers of calculation and mathematical reasoning (Howlin et al 2009; Treffert 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, areas of preserved memory processing have also been found (e.g. Assouline, Foley Nicpon, & Dockery, 2012; Boucher & Lewis, 1989; Boucher & Warrington, 1976; O’Shea, Fein, Cillessen, Klin, & Schultz, 2005) including exceptional memory skills (Bennett & Heaton, 2012; Mottron, Belleville, Stip, & Morasse, 1998). Southwick et al (2011) used a comprehensive test battery, the Test of Memory and Learning (TOMAL; Reynolds and Bigler, 1994), to broadly assess memory performance in ASD and found that the individuals with ASD performed significantly below age- and education-matched typically-developing comparisons (TDC), 5–19 years of age, across all domains of memory function.…”
mentioning
confidence: 99%